Exosomes from adipose-derived stem cells alleviate premature ovarian failure via blockage of autophagy and AMPK/mTOR pathway - Ren,Yu; He,Jinying; Wang,Xiao; Liang,Hongyu; Ma,Yuzhen (PeerJ, 2023)
Objective The objective of this study was to investigate the effects and mechanisms of adipose-derived stem cell-derived exosome (ADSCs-Exo) in treating premature ovarian failure (POF). Methods We constructed a POF mouse model through intraperitoneal injection of cyclophosphamide, followed by the administration of the autophagy inhibitor 3-methyladenine (3-MA). Pathological injury, follicle stimulating hormone (FSH), malondialdehyde (MDA), reactive oxygen species (ROS), estradiol (E2), superoxide dismutase (SOD), granulosa cell (GC) apoptosis, and autophagy were assessed. Exosomes isolated from ADSCs were used to treat POF in mice. The AMPK-mTOR pathway and its proteins (p-AMPK and p-mTOR) were evaluated. A POF cell model was established using cyclophosphamide-treated human ovarian granulosa-like tumor (KGN) cells. We administered ADSCs-Exo and rapamycin to validate the mechanism of ADSCs-Exo against POF. Results In POF mice, 3-MA treatment attenuated pathological injuries, decreased FSH, MDA, and ROS levels, and increased E2 and SOD levels. 3-MA treatment also inhibited GC apoptosis and autophagy. ADSCs-Exo alleviated pathological injuries, improved ovarian morphology and function, and reduced oxidative stress in POF mice. ADSCs-Exo inhibited GC apoptosis and autophagy. ADSCs-Exo downregulated the expression of AMPK/mTOR pathway proteins (p-AMPK and p-mTOR). In the POF cell model, ADSCs-Exo and rapamycin inhibited AMPK/mTOR-mediated autophagy. Conclusion ADSCs-Exo inhibits POF through the inhibition of autophagy and the AMPK/mTOR pathway. This study provides a potential target for the clinical treatment of POF.
Keywords: Adipose-derived stem cell; AMPK/mTOR pathway; Autophagy; Exosome; Premature ovarian failure